The Influence of Perceived Ease of use and Perceived Usefulness on the Intention to Reuse the Pintar Pay Application of KSP Pintu Air In Maumere City, Mediated by Trust - Botha, Yuslin Nursivin Dua; Khuzaini, Khuzaini; Lestariningsih, Marsudi (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2025)
The development of digital technology encourages cooperatives to transform their services through application-based systems, enhancing efficiency and member satisfaction. KSP Pintu Air, one of the largest cooperatives in Indonesia, has developed the Pintar Pay application to facilitate digital financial transactions for its members. However, the number of users of this application is still not proportional to the total number of cooperative members. This research aims to analyse the influence of perceived ease of use and perceived usefulness on the intention to use the Pintar Pay application, as well as the mediating role of trust in this relationship. The research approach employs a quantitative method, utilising Partial Least Squares (PLS) analysis on primary data collected from 354 respondents who use applications in the city of Maumere. The results show that perceived ease of use and perceived usefulness have a significant positive effect on the intention to use. Trust is proven to mediate the relationship between perceived ease of use and perceived usefulness on the intention to use. These findings highlight the importance of enhancing user trust through robust data security and system reliability to foster the adoption of digital cooperative applications.